An Examination of Library Anxiety at Cape Breton University - Lenard J. Lawless (Evidence Based Library and Information Practice, 2011)
Objective – Library anxiety as a phenomenon has been discussed for decades. While it is generally recognized, seeing its effects within a specific institution can often be difficult. This study examined the presence and degree of library anxiety among students at Cape Breton University in Canada. Methods – A modified version of the Library Anxiety Scale (LAS) was provided to the students via an online survey. Invitations to take the survey were sent to students by email and via the Student Union’s social networking site. Results – The average score on the LAS showed only mild anxiety levels among all the respondents. When categorizing the results by either program of study or program year, the results vary from no to mild anxiety. Little variation was seen between the sexes, with both males and females scoring close to the overall average of mild anxiety. Conclusions – With no segments of the student body scoring in the moderate to severe levels, the overall LAS scores for Cape Breton University’s students appear to be in a range that could be considered “normal.”